BALANCESHEET OF THE INSURANCE COMPANIESEND REINSURANCEVS.BALANCESHEET OFNON-INSURANCE (Research Bulletins of the Faculty of Economic Sciences, 2021)
Insurance activities conducted byinsurance companiesrequire adequateassets that would meet peculiar requirements specific for insurance business. Assets ofan insurance company is a formofguarantee for the finance entrusted by the insuredand moreover the insurance company is obliged to meet the expectationswith regard to the fulfillmentof insurance agreements. The differences between the financial statementsof an insurancecompany and the statements submitted by other entities is expressed mainly in the presentation of the balance sheet.
Keywords: insurancecompany, financial statement, balance sheet,assets, liabilities